Letter from the Editor - Charlene Downing (AOSIS, 2008)
When we stand at closing the door of this year we have to stand in the doorway and celebrate the many challenges and new beginnings we have experienced within the environment of Health SA Gesondheid. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.